2016
DOI: 10.1111/1754-9485.12471
|View full text |Cite
|
Sign up to set email alerts
|

SPECTCT/VQ versus CTPA for diagnosing pulmonary embolus and other lung pathology: Pre‐existing lung disease should not be a contraindication

Abstract: SPECT-CT/VQ has high sensitivity and specificity for diagnosing PE compared with CTPA, even among patients with pre-existing lung disease, with lower radiation doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…In routine V/Q SPECT imaging studies, the ventilation component may improve the specificity of the perfusion study and there is already data showing that the addition of low-dose CT to the SPECT images, the corroborated reporting of the scans with the structural information leads to a higher sensitivity, comparable with that of CTPA [ 20 , 21 ]. Cobes et al retrospectively analyzed V/Q SPECT/CTs in 5 patients hospitalized with COVID-19 and determined that V/Q SPECT/CT could play a role diagnosing embolic complications while following meticulous hygiene [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In routine V/Q SPECT imaging studies, the ventilation component may improve the specificity of the perfusion study and there is already data showing that the addition of low-dose CT to the SPECT images, the corroborated reporting of the scans with the structural information leads to a higher sensitivity, comparable with that of CTPA [ 20 , 21 ]. Cobes et al retrospectively analyzed V/Q SPECT/CTs in 5 patients hospitalized with COVID-19 and determined that V/Q SPECT/CT could play a role diagnosing embolic complications while following meticulous hygiene [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen diagnostic accuracy studies met the inclusion criteria. [26][27][28][29][30][31][32][33][34][35][36][37][38] Study characteristics are depicted in Table S1. Twelve (92%) were single-institution studies.…”
Section: Diagnostic Accuracy Studiesmentioning
confidence: 99%
“…The risk of bias in patient selection was judged as low, high, and unclear in three, 30,34,36 eight, 26,27,29,[31][32][33]37,38 and two 28,35 studies, respectively. Of the eight studies at high risk of bias, three did not enroll a consecutive or random sample of patients, 26,27,37 three had > 10% of the source population that was not analyzed, 29,33,38 and two excluded patients in whom tests were of poor quality or without final diagnosis. 31,32 In two studies, insufficient data were reported to permit a judgment and the risk of bias was judged as "unclear."…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations